2016
DOI: 10.31018/jans.v8i4.1125
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of happy seeder technology versus normal sowing in wheat ( Triticum aestivum) in adopted village Killi Nihal Singh of Bathinda district of Punjab

Abstract: Paddy- wheat crop rotation is dominant in the Punjab state covering about 28.40 lakh hectares of cultivable land. This paddy–wheat rotation also assesses the potential of new technology i.e. happy seeder technology to address the problem. The straw management system should be necessary for all the combine harvesters. The total 28 field demonstrations on happy seeder technology were conducted in village Killi Nihal Singh of district Bathinda of Punjab state during the years 2013-14 & 2014-15.The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…2174.25), which was mainly due to saving in land preparation labour cost. Dhillon [11] also reported similar results.…”
Section: Cost Of Cultivationsupporting
confidence: 60%
“…2174.25), which was mainly due to saving in land preparation labour cost. Dhillon [11] also reported similar results.…”
Section: Cost Of Cultivationsupporting
confidence: 60%
“…Additionally, storing the paddy straw in the field rather than burning it results in savings of about 3400 and 6200 ha −1 , respectively [130]. Therefore, net profitability is much higher with Happy seeder and turbo seeder type of sowing than conventional sowing [131,132]. When compared to conventional wheat crop raising techniques and other reduced tillage systems, the ZT fertilizer-cum-seed drill method was found to be the most economical and to have the best benefit-cost ratio [133].…”
Section: Profitabilitymentioning
confidence: 99%
“…Singh et al (2020) reported a significant decrease in grain yield under Happy seeder sowing compared to conventional sowing due to lack of experience and non-adoption of site-specific component technologies for Happy seeder. In contrast, Dhillon (2016) and Sidhu et al (2015) reported a slight increase in yield under Happy seeder sowing over conventional sowing. The varieties did not differ significantly in grain yield, except in the second year where variety PBW 725 produced significantly higher yields than HD 3086.…”
Section: Grain Yieldmentioning
confidence: 77%